Strategi Pendampingan Pastoral Bagi Jemaat Di Era Pandemi Covid-19 - Marnaek Nainggolan (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
One of the most difficult things for pastors during the coronavirus pandemic is the challenge of providing pastoral care to the church member in times of physical distancing by implementing health protocols. Ready or not ready for various adaptations have occurred, in pastoral care. The era of Covid-19 has led to all social structures globally, including the church ministry community. a pandemic on the congregation that causes unrest, social, emotional, psychological and economic impacts that change the physical face of the church and congregation. When church members struggle financially, the church, church members are greatly affected by the currency experience, the church also faces financial instability. Pandemic and increasing inequalities existing inequalities among church members. As pastors of the congregation, it is proper to accompany them in the midst of this prolonged crisis. However, nowadays many shepherds have difficulty in carrying out face-to-face mentoring services in connection with the pandemic period which has not ended until now. Even though the pandemic era has lasted for two years, many people are still worried about carrying out various activities as they usually did before the Covid-19 era. The purpose of this research is to get the right strategy so that it can be implemented during the Covid-19 pandemic. using qualitative research methodologies; The method used is descriptive qualitative through research on various relevant literature using a biblical perspective, conducting qualitative analysis by selecting and researching six strategies for pastoral care services for congregations in the Covid-19 Pandemic era and research results from journals in the last five years. From the results of the study, it can be said that it is necessary to implement relevant pastoral care strategies in the era of the Covid-19 pandemic by taking the important values of the six pastoral care strategies studied.